Self-selection from higher education: a meta-review of resources for academic decision-making of mainstream and underrepresented students. Issue 3 (3rd July 2022) - Vietze, Jana; van Herpen, Sanne G. A.; Dias-Broens, Aike; Severiens, Sabine E.; Meeuwisse, Marieke
ABSTRACT: Self-selection refers to the decision of qualified students to not pursue their highest possible educational degree, including higher education. In this systematic meta-review, we used the conceptual framework of college choice to identify resources or mechanisms for students' self-selection from higher education in international reviews and meta-analyses. In addition, we investigate whether underrepresented student groups (i.e., first-generation and cultural minority) experience unique resources and mechanisms for self-selection. Our narrative synthesis of international reviews and meta-analyses indicated that self-selection is related to financial, informational, social, aspirational resources in all contextual layers (i.e. individual habitus, school and community, higher education, socio-political context) of the conceptual framework of college choice. Whereas the family can help prevent self-selection by providing all four types of resources, school and higher education institutions can provide important information and social support through counselling and mentoring activities. For underrepresented groups, vertical and horizontal transmissions of social capital and experienced personal fit with the higher education environment may be of special importance for preventing self-selection. We conclude by discussing the potential of self-selection as concept for future interventions and research on widening access to higher education.